(untitled) (Swiss Medical Weekly, 2013)
BACKGROUND: A small proportion of patients with influenza H1N1 rapidly develop acute respiratory failure and are a problem for intensive care units (ICUs). Although certain clinical risk factors have been identified, few measurable biochemical/haematological markers able to predict poor outcome have been reported. The aims of the present report are to show which variables on and during admission are associated with increased in-hospital mortality in patients admitted to the ICU with acute respiratory failure due to H1N1 influenza. METHODS: A prospective observational study at two ICUs was carried out between August 2009 and March 2011. The study period covered two waves of pandemic influenza A H1N1 in Spain. Clinical and laboratory data on and during ICU admission were recorded for the purpose of analysis. RESULTS:Sixty patients with acute respiratory failure due to H1N1 influenza were admitted during the period described above; 63.3% (n = 38) were male and the mean age was 49.2 ± 14 years. Regarding comorbidities, 46.7% (n = 28) were smokers, 38% (n = 23) had hypertension, 30% (n = 18) had a body mass index (BMI) >30 kg/m2, 30% (n = 18) had chronic obstructive pulmonary disease and 26% (n = 16) had cardiac insufficiency; 16.6% (n = 10) had bacterial co-infection, 70% (n = 42) required invasive mechanical ventilation and 48.3% (n = 29) non-invasive mechanical ventilation. Mortality was 20% (n = 12). Comparing survivors with non-survivors, univariate analysis revealed significant differences in BMI, creatinine, haemoglobin, platelets, arterial pH, pCO2, and the rate of bacterial co-infection. In the multivariate analysis, only the presence of lower platelet count was statistically significant (214 ± 101 vs 113 ± 82 ×109/L; p= 0.009). Patients with thrombocytopenia showed a lower in-hospital survival rate (55%vs92.5%; Log Rank = 0.008). CONCLUSIONS:Thrombocytopenia could be valuable marker of in-hospital mortality in patients with respiratory failure due to H1N1 influenza in the ICU scenario.